Feasibility of portable continuous laryngoscopy during exercise testing. Issue 1 (4th February 2019) - Hull, James H.; Walsted, Emil S.; Orton, Christopher M.; Williams, Parris; Ward, Simon; Pavitt, Mathew J.
Exercise-induced laryngeal obstruction (EILO) is a prevalent and yet still under-recognised cause of exertional breathlessness [1]. The transient closure of the larynx, which develops during EILO, results in dyspnoea, cough, inspiratory wheeze ( i.e. stridor) and tightness in the throat on physical exertion. It is estimated that EILO is present in 6% of adolescents and as many as one in four athletes with unexplained respiratory symptoms [1, 2]. Despite improved recognition over the past 5 years [3, 4], it remains frequently misdiagnosed and mistreated as asthma [2, 5]. Exercise-induced laryngeal obstruction (EILO) is a prevalent problem causing exertional breathlessness and wheeze. This report demonstrates the feasibility and safety of a diagnostic approach to EILO, using a portable laryngoscope during exercise. http://ow.ly/eM6L30njDst